STRATEGIC COST MANAGEMENT AND BUDGETING (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In the current conditions of globalization and a growing competitive environment, strategic cost management is becoming a very relevant direction. This direction became of particular importance in the context of the financial crisis. The main program used for strategic cost management is budgeting technology. That is why we consider it important to consider the conceptual foundations of the emergence and development of budgeting, as well as the fact that it is a modern method for determining costs and Planning, first of all, to analyze the practical significance of it in the organization of cost accounting by Centers of responsibility.